Manufacturing Process Design and Costing An Integrated Approach - Grewal, Simmy. (Springer London : Imprint: Springer, 2011)
Contract manufacturing is growing rapidly worldwide and this is creating a need for innovative manufacturing information systems that can effectively integrate process design and costing data in order to allow 'what if' scenario assessments to be done rapidly. Manufacturing Process Design and Costing details the development of such an information system with a focus on the data schema and user interface design. The software facilitates integration of part manufacture, assembly planning and assessment of associated costs in a concurrent manner. The benefits this methodology has provided to industry and its usefulness as a teaching aid are outlined. Manufacturing Process Design and Costing illustrates effective integration of the variables involved. A novel user interface design allows the capture of process know-how, resulting in the decoupling of process design knowledge from personnel turnover issues, hence ensuring the maximisation of an organisation's ability to respond to business opportunities. Manufacturing Process Design and Costing is written for professionals in the manufacturing industry and academics. Simmy Grewal is the founder and managing director of Simsoft Knowledge Systems Pty Ltd. The company was founded in 1998 to commercialise the results of research he led at the Australian Government research agency CSIRO. From 2003 to 2005 he also held the position of Professor of Product and Process Design under the Distinguished Professionals Scheme in the Department of Industrial and Systems Engineering of The Hong Kong Polytechnic University, where he lectured and researched in the area of process design and knowledge management. His career prior to joining CSIRO was in academia and industry in the UK and Ireland.